Study of fetomaternal outcome in oligohydramnios in term pregnancy and its correlation with non-stress test - Naykodi, Priti S.; Ghogare, Aishwarya N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: A reduced volume of amniotic fluid, known as oligohydramnios, complicates about 1-5% of pregnancies and is frequently linked to poor perinatal outcomes. A diagnostic criterion for oligohydramnios is an amniotic fluid index (AFI) of ≤5 cm. The AFI is used to quantify the volume of amniotic fluid. The purpose of this study was to examine the perinatal outcomes in term pregnancies with oligohydramnios and compare them to the findings of the non-stress test (NST), a test used to evaluate the health of the fetus. Methods: A tertiary care hospital held this prospective observational study. One hundred pregnant women with singleton term pregnancies (≥37 weeks gestation) who have been diagnosed with oligohydramnios (AFI≤5 cm) are included in this study. Demographic information, NST results, delivery method, and perinatal outcomes were gathered and analyzed using the proper statistical techniques. Results: The study population’s mean age was 25.12. Women who were multigravida made up 71% of the participants. Fetal distress was the main indication (56%), and the rate of lower segment cesarean section (LSCS) was 43%. A higher rate of LSCS (87%), low birth weight (<2.5 kg) (69.6%), and NICU admission (26%) were all substantially correlated with a non-reactive NST. Conclusions: Oligohydramnios during term pregnancy is associated with a high incidence of LSCS. A non-reactive NST in the presence of oligohydramnios is a strong predictor of poor perinatal outcomes, such as increased rates of operative delivery, low birth weight, and NICU admission. As a result, careful fetal surveillance, including NST, is critical in managing such pregnancies in order to improve perinatal outcomes.